2006
DOI: 10.1111/j.1365-2303.2006.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the ThinPrep Pap test and conventional cytology results in a Canadian cohort

Abstract: In this population, ThinPrep was superior to the conventional Pap test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
10
2
Order By: Relevance
“…Our prevalence rates were very similar to those reported in the study of Turkish Cervical Cancer and Cervical Cytology Group (Turkish Cervical Cancer And Cervical Cytology Research Group 2009), an extended investigation in Turkey. But, the rates of the present study were much lower than the ones reported for Western populations, in general (de Sanjose et al, 2003;Duggan et al, 2006;Kroupis et al, 2007;Kulig et al, 2010;Marques et al, 2011). However, our results were very similar to those reported from other Islamic countries like Saudi Arabia, Egypt, and Iran (Jamal et al, 2003;elAll et al, 2007;Nokiani et al, 2008) that may be ascribed to low prevalence of HPV (Tuncer et al, 2006;Ozalp et al, 2012), religion, or the conservative cultures, akin to Turkish population.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Our prevalence rates were very similar to those reported in the study of Turkish Cervical Cancer and Cervical Cytology Group (Turkish Cervical Cancer And Cervical Cytology Research Group 2009), an extended investigation in Turkey. But, the rates of the present study were much lower than the ones reported for Western populations, in general (de Sanjose et al, 2003;Duggan et al, 2006;Kroupis et al, 2007;Kulig et al, 2010;Marques et al, 2011). However, our results were very similar to those reported from other Islamic countries like Saudi Arabia, Egypt, and Iran (Jamal et al, 2003;elAll et al, 2007;Nokiani et al, 2008) that may be ascribed to low prevalence of HPV (Tuncer et al, 2006;Ozalp et al, 2012), religion, or the conservative cultures, akin to Turkish population.…”
Section: Discussioncontrasting
confidence: 80%
“…Hitherto, different studies have exhibited the major and substantial variations considering the rates of ASCUS, LSIL, HSIL, AGUS, and cervical cancer (Forman 2003;Sanjose et al, 2003;Altaf 2006;Duggan et al, 2006;Turkish Cervical Cancer And Cervical Cytology Research Group, 2009;Castle et al, 2010;Kulig et al, 2010). In the present study, 1.83% of the Pap smears had the abnormal cytology, with ASCUS in 1.18%, LSIL in 0.39, HSIL in 0.16%, AGUS in 0.07%, squamous cell carcinoma in 0.02%, and adenoarcinoma in 0.006%.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the often conflicting results from other studies, [7][8][9][10][11]18,23 we found with a high level of evidence that LBC leads to significantly higher proportions of SBLB ec2 results. The reason for this observation is unclear.…”
Section: Resultscontrasting
confidence: 56%
“…This was considered of relevance in view of previous studies that reported increased numbers of tests without endocervical cells while using LBC. [7][8][9][10][11] In addition, the clinical relevance of unsatisfactory results was assessed with follow-up cytology and histology. …”
mentioning
confidence: 99%
“…2 However, there is a scientific debate if the application of LBP over the conventional Pap smear (CP) has improved the clinical effectiveness in cervicovaginal specimen collection and handling, and if LBP is cost beneficial. [3][4][5][6][7] To our knowledge, studies that have compared the overall performance advantage of LBP over CP have assessed only the rate of specimens considered as "Unsatisfactory for Evaluation." 7,8 We conducted a retrospective comparative caseseries study with the primary objective of evaluating the overall performance of LBP with CP, where the overall performance was defined as the sum of the adjusted proportions of unsatisfactory and rejected specimens.…”
mentioning
confidence: 99%